Efektifitas Ekstrak Nannochloropsis oculata Terhadap Peningkatan Kepadatan Kolagen pada Proses Penyembuhan Alveolar Osteitis. - Ajeng Saghita Enggardini; Syamsulina Revianti; Noengki Prameswari (Denta: Jurnal Kedokteran Gigi, 2021)
Background: Alveolar osteitis was one complication after tooth extraction. This condition remains a common post operative problem that results in severe pain and inhibit socket healing. Nannochloropsis oculata’s extract contains alkaloids, carotenoids, flavonoids, terpenoids and tocopherols that could accelerate the wound healing process. Purpose: Examine the effectivity of Nannochloropsis oculata extract to the increased density of collagen in alveolar osteitis healing process. Materials and Methods: This research design was post-test only control group design, using 64 male Wistar rats then divided into two major groups. Group 1 (irrigation) and group 2 (dressing). In each group contains a negative control group (irrigation PBS or dressing PBS), positive control group (irrigation Saline 0,9% or dressing Alvogyl), and the treatment group (irrigation or dressing used Nannochloropsis oculata extract 2,5% and 5%). After treatment on the 3rd and 7th day, rats were euthanazied than collagen density was measured at histopathology slide used Masson’s Trichom with magnification 100x under light microscope, than it what measured. Data was analyzed with Kruskal-Wallis and Mann-Whitney test. Result: There were significant differences of collagen density beetwen irrigation treatment groups (0,045), but there were not significant differences beetwen dressing treatment groups (0,243). Dressing method was more effective to increase collagen density than irrigation groups (0,026). Conclusion: Dressing treatment used Nannochloropsis oculata extract concentration 5% was most effective to increased the collagen density in alveolar osteitis healing process on 7th days.